Strategi Keunggulan Kompetitif Penjualan Ikan Lele Pada Raja Lele Lestari Desa Pagu Kecamatan Wates Kabupaten Kediri - Muhamad Abdul Ghoni; Moch. Saleh Udin; Taufik Akbar (STIKes Ibnu Sina Ajibarang, 2023)
Competition in business is getting tougher, as evidenced by the variety of products released by business people to survive the competition. Increasingly tight business competition requires companies to have their own competitive advantages. Many consider competitive advantage to be a weapon used by companies in the hope of making the company win over its competitors. Raja Lele Lestari is a business that operates in the field of catfish cultivation in Kediri Regency. This research aims to analyze the Competitive Advantage Strategy of Raja Lele Lestari in increasing sales. This research uses descriptive qualitative methods and SWOT analysis along with the BCG matrix. Data collection was carried out by observation, interviews and documentation. The analysis results obtained in this research show that the analysis shows a very profitable correlation, BCG shows that the company's market share is still low and the SWOT analysis has a SO strategy solution to overcome this which can ultimately support Raja Lele Lestari to reach the peak of competitive advantage.